TRIBES OF THE ANAMALAIS LIVELIHOOD AND RESOURCE ‐ USE PATTERNS OF COMMUNITIES IN THE RAINFORESTS OF THE INDIRA GANDHI WILDLIFE SANCTUARY AND VALPARAI PLATEAU - MANISH CHANDI (NATURE CONSERVATION FOUNDATION, 2008)
The Western Ghats hill range of India, recognised as a global biodiversity hotspot, also contains impressive cultural diversity including a number of tribal communities. This study uses past records and primary field research to describe aspects of ethnic identity, social change, demography, livelihoods, and resource use among three tribal communities in the Anamalai hills along the Western Ghats mountains of southern India. Kadar, Muthuvar, and Malai Malasar communities across 190 households in 8 settlements located adjacent to rainforests in the Indira Gandhi Wildlife Sanctuary were studied to examine current modes of existence vis-à-vis their past and the use of rainforest patches they live within. The tribal communities surveyed are sedentary compared to their past livelihood as nomadic hunter-gatherers and shifting cultivators in the region. They are distinguished by dialects a nd customs despite considerable change and acculturation. Demographic changes include a 180% increase in population over three decades and increasing literacy and access to higher education with a current literacy rate of 52% (females: 42%, males: 63%). Livelihood activities range from natural resource gathering for income generation, cultivation of subsistence and cash crops and limited employment with the Forest department and at private plantations. Though natural resource gathering has been in vogue from early records, economic transformation toward other employment opportunities is evolving given restrictions in collecting forest produce. Some settlements have diversified through cash crop cultivation, especially cardamom (producing over 2,700 kg in 2006), although benefits are marginal, given available space, cultivation practices, and fluctuating prices. Despite changes in housing and water supply infrastructure, the required repair and improvements in settlements, offer opportunities to develop relationships between managers and local tribes people. There is considerable ground to cover in developing sustainable sources of income and livelihood given these developments. The possible implications of these strategies on rain forest conservation and experiential changes in their cultural sphere are also briefly deliberated on advocating possible beginnings toward co-management. It is essential that inherent skills, though scarce, are used to derive alternative employment and manage income sources, given the twin needs of a growing population and conservation of the biologically diverse rain forest ecosystems they live amidst.